Modeling, thermodynamic and techno-economic analysis of coal-to-liquids process with different entrained flow coal gasifiers. (1st November 2018) - Qin, Shiyue; Chang, Shiyan; Yao, Qiang
Highlights: Modeling of coal-to-liquids (CTL) process with different entrained flow gasifiers was conducted. Thermodynamic analysis of CTL process was presented. Locations and magnitudes of exergy inefficiencies were identified and quantified. Techno-economic and CO2 emissions analysis of CTL process were conducted. Abstract: For the coal-to-liquids (CTL) plant, the most important unit is gasification, which determines the composition of the crude syngas, and affects CO2 emissions and investment of the CTL process. This paper conducts a detailed plant-wide modeling of CTL process with different entrained flow gasifiers. The model is compared with the literature data. Three cases of CTL process with different entrained flow gasifiers (GSP, Shell and Texaco) are researched through thermodynamic, techno-economic and CO2 emissions analysis. Case GSP represents the CTL process with GSP gasifier, Case Shell represents that with Shell gasifier, and Case Texaco represents that with Texaco gasifier. For a typical CTL process, Case GSP can produce FT liquids of 277.49 t/h, Case Shell can produce 246.25 t/h, and Case Texaco can provide 232.93 t/h. The energy efficiencies of Case GSP, Shell and Texaco are 50.85%, 48.18% and 41.09%, respectively. The exergy efficiencies are 49.89%, 47.20% and 40.44%, respectively. The exergy inefficiencies of the subsystem are quantified. The economic performance and CO2 emissions of the three cases are also discussed.